Предмет: Алгебра,
автор: HadasChannel
Помогите пожалуйста. Номер 457 а)
Приложения:
Ответы
Автор ответа:
0
(a+b/(a-b)^2 - a/(a-b)*(a+b)) * a-b/b*(a+b) =
= (a+b-a/(a-b)^2) * a-b/b*(a+b)=
= b*(a-b)/(a-b)^2*b*(a+b)=
= 1/ a+b
= (a+b-a/(a-b)^2) * a-b/b*(a+b)=
= b*(a-b)/(a-b)^2*b*(a+b)=
= 1/ a+b
Похожие вопросы
Предмет: Математика,
автор: babuskababuska306
Предмет: Химия,
автор: 44567893
Предмет: Французский язык,
автор: Aanuto4ka
Предмет: Химия,
автор: taskaevalex200
Предмет: География,
автор: tat999ka